Variació i estàndard - Bibiloni, Gabriel (Caplletra. Revista Internacional de Filologia, 1998)
The nature of linguistic variation is governed by the character and the scope of the networks of interaction, and the frequencies and intensity of communications inside those networks. Standardization, in a complete sense, represents a substantial modification of the conditions of interaction: basically, it expands, structures and consolidates the communicative network. The spread of the standard variety thus acts on the initial conditions, modifying them significantly. As a referential model, the standard reducesgeographical variation, imposing specific limitations on the maintenance of forms which are restricted geographically and which have attained social prestige. Standardization also shapes social variation; it establishes or increases the pre-existing correlations between social status and linguistic variants, on occasion inside the framework of another standard. Finally, by expanding the number of contexts of use of the language, standardization acts as a factor of functional and stylistic diversification.